TRANSITIONAL JUSTICE: : ARE TRUTH AND RECONCILIATION COMMISSIONS WORTH IT? - Triantaphyllis, Christian (Revista dos Estudantes de Direito da Universidade de Brasília, 2012)
Truth and reconciliation commissions are becoming an increasingly popular method used by the international community towards promoting transitional justice. However, many victims of human rights violations resort to further means of pursuing justice even after a truth and reconciliation commission has been engaged, which brings the question of whether truth and reconciliation commissions are worth the time and money they require. Incomplete justice and tokenism are among the reasons that it can be argued that a truth and reconciliation commission is not an efective alternative in facilitating reparations after human rights atrocities have occurred. Te following analysis explores this question and eventually identifes valuable transitional justice outcomes that are unique to truth and reconciliation commissions.